NOD2 PROMOTES HOST DEFENSE AND RECOVERY INDUCING MACROPHAGE-MEDIATED INNATE LYMPHOID CELLS TYPE 3 ACTIVATION FOLLOWING FUNGAL INFECTION IN EXPERIMENTAL COLITIS. (22nd January 2022) - McAndrew, Morgan; Havran, Hannah; Di Martino, Luca; Ghannoum, Mahmoud; Pizarro, Theresa; De Salvo, Carlo
Abstract: Recent studies have documented the complexity of the intestinal fungal community ('mycobiome') in mice, and clinical and experimental observations have shown that the mycobiome influences both gut health and disease, e.g., inflammatory bowel disease (IBD). In fact, prior studies have shown that Crohn's disease (CD) patients, compared to healthy controls, harbor higher levels of intestinal Candida tropicalis (Ct), which is the major fungal species detected in the colons of colitic mice after DSS challenge. More recently, Debaryomyces hansenii (also known as Candida famata ) has been found in intestinal wounds of mice and inflamed mucosal tissues of CD patients. Moreover, proteins encoded by genes within IBD susceptibility loci, such as the pattern recognition receptor (PRR), NOD2, are known not only to recognize bacterial components, but also a fungal cell wall element, chitin. In fact, the role of PRRs in regulating immunity against intestinal fungi, and how fungi influence IBD remains poorly defined. We challenged DSS colitic WT and Nod2 -/ - mice with Ct 2 days before DSS administration and subsequently on day (d)0, 3 and 6. Our data confirms previous studies that Ct challenge does not exacerbate colitis in DSS-treated C57BL/6 wildtype (WT) mice, however, Ct-infected Nod2 -/ - mice possess a higher fungal burden and exhibit worse colitis symptoms, such as weight loss, decreased stool consistency, and presence of blood in stools, vs. Ct-infected WT mice, indicating an essential and protective role for NOD2 during colitis recovery after Ct challenge. Our results also show that Ct-infected Nod2 -/ - mice display a marked reduction in colonic Il22 and Il17, which are cytokines previously reported to be important in maintaining epithelial barrier integrity during DSS colitis, These data were confirmed in colons of Ct infected DSS challenged, ileitis-prone SAMP1/YitFc (SAMP) mice that were deficient in NOD2. Moreover, Our in vitro data show, a decrease in Il1b and Il23 in bone marrow-derived macrophages from SAMP Nod2 -/ - mice compared to WT after 2h of exposure to chitin. IL-17 + innate lymphoid cells (ILCs) are also known to control fungal burden during opportunistic fungal infections, and interestingly, our findings indicate that Ct infection of Nod2 -/ - vs. WT mice results in a decreased frequency of mesenteric lymph node–derived type 3 ILCs (ILC3s), suggesting that delay in fungal clearance and recovery in Nod2 -/ - mice may be due to the inability to mount protective type 3 immune responses. Taken together, the data so far collected suggests that NOD2 is essential to maintain gut mycobiome homeostasis and drives protective innate immune responses, via a macrophage-mediated ILC3 recruitment and IL-17 mechanism, by preventing the overgrowth of opportunistic fungi that may contribute to chronic intestinal inflammation, such as that observed in CD.